First Isolation of Leishmania from Northern Thailand: Case Report, Identification as Leishmania martiniquensis and Phylogenetic Position within the Leishmania enriettii Complex - Pothirat,T. (Public Library of Science, 2015)
© 2014 Pothirat et al. Since 1996, there have been several case reports of autochthonous visceral leishmaniasis in Thailand. Here we report a case in a 52-year-old Thai male from northern Thailand, who presented with subacute fever, huge splenomegaly and pancytopenia. Bone marrow aspiration revealed numerous amastigotes within macrophages. Isolation of Leishmania LSCM1 into culture and DNA sequence analysis (ribosomal RNA ITS-1 and large subunit of RNA polymerase II) revealed the parasites to be members of the Leishmania enriettii complex, and apparently identical to L. martiniquensis previously reported from the Caribbean island of Martinique. This is the first report of visceral leishmaniasis caused by L. martiniquensis from the region. Moreover, the majority of parasites previously identified as “L. siamensis” also appear to be L. martiniquensis.